Development and challenges of anaerobic digestion application in wastewater treatment - Hassan, Azman (Faculty of Chemical & Natural Resources Engineering, 1991)
There has been an increasing interest in the application of anaerobic digestion for the treatment of industrial wastewater. This is due to the recent advances in bioscience and biochemical process engineering. This paper outlines the potential beneficial aspects of the anaerobic process for methane production from industrial wastes and describes some recent developments in anaerobic digestion technology. Discussion on the environmental factors effecting the process is included.